2004
DOI: 10.1038/sj.ijir.3901260
|View full text |Cite
|
Sign up to set email alerts
|

A new atypical antipsychotic: quetiapine-induced sexual dysfunctions

Abstract: In this paper, we evaluated the new antipsychotic, quetiapine-induced sexual dysfunctions (SDs). The study group consisted of 36 patients with schizophrenia receiving quetiapine. The changes in general sexual functions were assessed by using Arizona Sexual Experience Scale (ASEX) and Udvalg for Kliniske Undersogelser (UKU) Side Effect Rating Scale at baseline and week 4. Also, prolactin (PRL) values were determined at baseline and week 4. There was statistically significant difference with respect to the mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 7 publications
1
22
1
1
Order By: Relevance
“…Unlike the more traditional and lengthy scales for assessing sexual dysfunctions, the ASEX can be completed in approximately 5 minutes 27 , it is a brief 5-item questionnaire designed to measure sexual functioning in the following domains: sexual drive, arousal, penile erection/vaginal lubrification, ability to reach orgasm, and satisfaction with orgasm over the past week 25 . The frequency of sexual dysfunctions was very high, a finding consistent with previous studies conducted in different countries 6,11,15,[32][33][34][35] . Females had a much higher rate (79.2%) than males (33.3%).…”
Section: Discussionsupporting
confidence: 80%
“…Unlike the more traditional and lengthy scales for assessing sexual dysfunctions, the ASEX can be completed in approximately 5 minutes 27 , it is a brief 5-item questionnaire designed to measure sexual functioning in the following domains: sexual drive, arousal, penile erection/vaginal lubrification, ability to reach orgasm, and satisfaction with orgasm over the past week 25 . The frequency of sexual dysfunctions was very high, a finding consistent with previous studies conducted in different countries 6,11,15,[32][33][34][35] . Females had a much higher rate (79.2%) than males (33.3%).…”
Section: Discussionsupporting
confidence: 80%
“…Overall, these adverse events are consistent with quetiapine's pharmacology, perhaps with the exception of increased desire for sex. While studies have found antipsychotics, including quetiapine, to typically decrease libido (Atmaca et al 2005;Novick et al 2009), case reports of increased libido have also been found in the clinical literature (Menon et al 2006). In short, while quetiapine was generally well tolerated in this study (only one dose-reduction requested), identifying an optimal dose that can maximize both tolerability and efficacy remains a priority.…”
Section: Discussionmentioning
confidence: 87%
“…Melkersson has also reported an overall sexual dysfunction of 89% due to risperidone. [15] Up to 93% of risperidone-treated patients reported an overall impairment of sexual functioning in yet another study. [16] Even in the case of olanzapine and quetiapine, a frequency of overall sexual impairment, comparable to our study, was observed in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Of late, another study reported that impaired desire (44%) was the most common sexual dysfunction due to risperidone. [15] One more study reported that impaired libido is commonly seen even with quetiapine. [19] These finding are supported by the present study, which reports an impaired libido of 80% with risperidone, 72% with quetiapine, and 78% with olanzapine.…”
Section: Discussionmentioning
confidence: 99%